Oral Hygiene Education: Historical Evolution, Contemporary Evidence, and Future Perspectives - Gülhan Ünal (Journal of Kocaeli Health and Technology University, 2026)
Background: Toothbrushing remains the cornerstone of daily plaque control and the primary self-care intervention for preventing gingivitis and periodontitis. Since the early twentieth century, numerous manual toothbrushing techniques have been introduced to improve plaque removal and periodontal health. Despite decades of research, uncertainty persists regarding the superiority of individual brushing techniques and their effectiveness in routine clinical practice.Objective: This narrative review aims to summarize the historical evolution of manual toothbrushing techniques, critically evaluate the available scientific evidence comparing these techniques, and discuss current clinical recommendations for oral hygiene instruction.Methods: A narrative review was conducted using historical publications, landmark clinical studies, randomized controlled trials, systematic reviews, meta-analyses, and international clinical practice guidelines related to manual toothbrushing techniques and oral hygiene education. The literature was synthesized chronologically to illustrate the evolution of toothbrushing from empirical cleaning practices to evidence-based preventive care.Results: Toothbrushing techniques have evolved from simple mechanical cleaning methods to biologically oriented plaque-control approaches based on periodontal science. Classical techniques, including those described by Charters, Stillman, Fones, Bass, and Modified Bass, were developed to address specific clinical objectives rather than to establish a universally superior brushing method. Contemporary systematic reviews indicate that no manual toothbrushing technique consistently demonstrates clear superiority in reducing plaque accumulation or gingival inflammation. Instead, patient motivation, manual dexterity, adherence, individualized instruction, and regular professional reinforcement appear to play a greater role in determining long-term clinical outcomes.Conclusions: Current evidence suggests that successful oral hygiene education should prioritize individualized patient instruction rather than exclusive emphasis on a specific toothbrushing technique. Future developments are expected to integrate behavioural science, digital health technologies, and personalized preventive strategies to improve long-term oral hygiene behaviour.